Application of The Discovery Learning Model in Improving PAI Learning Outcomes in Class X Students SMAIT Mahmudiyyah - Hakim, R. Lucky Lukmanul; Toyyibah; Muawanah; Suminta, Rini Risnawita; Nisa, Ida Amiratun (Proceeding International Conference on Education, 2023)
This presentation is based on the results of classroom action research which aims to improve achievement student learning through the application of the Discovery Learning Learning Model in subjects Islamic Religious Education and Character Education in class X-MIPA-Putra SMAIT Mahmudiyyah Regency Sukabumi, West Java province. This research includes an assessment of student participation, implementationteacher learning, and achievement of student learning outcomes. Through two research cycles, the dataobtained from observations of student activities, assessments of teacher learning implementation, and testsstudent learning outcomes. The findings show that the use of the Discovery Learning Model canimprove student learning achievement, which was initially relatively low in cycle I, but has increasedsignificant in cycle II. This study confirms that the Discovery Learning Model is effective inincreasing the competence of Islamic Religious Education in class X-MIPA-Putra students at SMAITMahmudiyyah, Sukabumi district, West Java province.